Reactions to graphic and text health warnings for cigarettes, sugar-sweetened beverages, and alcohol: An online randomized experiment of US adults - Hall, Marissa G. (Prev Med, 2020)
We aimed to examine reactions to graphic versus text-only warnings for cigarettes, SSBs, and alcohol. A convenience sample of US adults completed an online survey in 2018 (n=1,352 in the analytic sample). We randomly assigned participants to view a: 1) text-only warning without efficacy information (i.e., message intended to increase consumers’ confidence in their ability to stop using the product), 2) text-only warning with efficacy information, 3) graphic warning without efficacy information, or 4) graphic warning with efficacy information. Participants viewed their assigned warning on cigarettes, SSBs, and alcohol, in a random order. Across product types, graphic warnings were perceived as more effective than text-only warnings (p<.001) and led to lower believability, greater reactance (i.e., resistance), more thinking about harms, and lower product appeal (all p<.05); policy support did not differ. Compared to SSB and alcohol warnings, cigarette warnings led to higher perceived message effectiveness, believability, fear, thinking about harms, policy support, and greater reductions in product appeal (all p<.05). The efficacy information did not influence any outcomes. Graphic warnings out-performed text-only warnings on key predictors of behavior despite causing more reactance.